Youth Knowledge Fair 2018 Engaging in Discussion on Climate Change ... : tracking change Local and Traditional Knowledge in Watershed Governance ... - Tracking Change (University of Alberta Library, 2018)
From May 16 – 18, 2018 the University of Alberta (Edmonton) hosted a poster competition and Indigenous Knowledge Fair for high school students from across western and northern Canada. The Tracking Change project recognizes that many peoples in the Mackenzie River Basin, specifically Indigenous peoples, have valuable insights about the social and environmental sustainability of the Basin. As such the importance of youth engagement is emphasized by project partners in terms of research priorities and key issues for study. Tracking change is investing in the development, research skills, knowledge sharing and relationship building between the next generation of knowledge holders in the Mackenzie River Basin. ...